Lietuvos mokslų akademijos bibliotekos XVII a. lituanikos fondo knygų ženklai - Braziūnienė, Alma (Knygotyra, 1993)
In this article the Lithuanian bookplates of the 17th century (i.e. superexlibris, exlibris, book stamps and inscriptions by the book owners) from the library of Lithuanian Academy of Science are analysed.There are 1255 books in the fund of Lituanica of the 17th century and there are 453 bookplates in these books. There are 208 inscriptions made by the book owners in these bookplates.The inscriptions by the book owners are divided into 3 groups: proveniential, memorial and dedicational. The first group is the largest. It shows whose the book was but doesn’t show how it was acquired. These inscriptions usually begin with words „Ex libris“, „Ex catalogo“, „Ex Bibliotheca“. The memorial inscriptions show how the owner acquired the book. The dedicational inscriptions indicate to whom the book was presented by the author or the other person. The majority of these inscriptions is from the libraries of monasteries (Dominican, Jesuits, Karmelit etc.). All inscriptions are in Latin and Polish.Exlibris, superexlibris and book stamps are made in the 18–19th centuries. They are in the books from the Library of Lithuanian Ortodoxical Seminary (there are 83 books with exlibris), Wrublewski’s library (35 books), A. Tiszkiewicz’s collection (28 books) etc..The investigation of bookplates gives a wide coverage of the social and cultural life of these centuries.